Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pemilihan Pasar Tradisional Sebagai Tempat Berbelanja (Studi Kasus Pada Pasar Tradisional Di Kabupaten Sleman) - Pramudyo, Anung (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2015)
This study examines the analysis factors that influence the decision as a shop in traditional market in Sleman. Based on theory, several variables has been constructed. TheyÂ  are product, price, location, service, and facility. This research was executed in traditional market in Sleman with 100 participants. The results supported price, location, and facility has strong predictive to the decision as a shop in traditional market in Sleman, but product and service has not influence to the decision as a shop in traditional market in Sleman. The analysis also found the result that simultaneously the product, price, location, service, and facility effected the decision as a shop in traditional market in Sleman.Keywords : product, price, location, service, facility, and decision as a shop in traditional market